2020
DOI: 10.1103/physreva.101.013404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vacancy defects in solid high-order harmonic generation

Abstract: The present work discusses the impact of vacancy defects in solid high-order harmonic generation. The total energy cut off of the high-order harmonic spectrum increases as a function of concentration of vacancy defect, and the total spectrum gradually turns into a single slanted spectrum without having an abrupt transition between primary and secondary plateaus. The spectral intensity of the below band-gap harmonics in a solid with vacancy defects is enhanced significantly in comparison to the harmonics in a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…However, in this case, the irregularity is induced by breaking the lattice periodicity by random shifts of ionic locations. Very recently, the appearance of ill-resolved electron trajectories in the Gabor profile of systems with vacancies were related to the interference of additional paths for the electron dynamics introduced by the defect states [49].…”
Section: B Effects Of Vacancies On the Hhg Spectramentioning
confidence: 99%
“…However, in this case, the irregularity is induced by breaking the lattice periodicity by random shifts of ionic locations. Very recently, the appearance of ill-resolved electron trajectories in the Gabor profile of systems with vacancies were related to the interference of additional paths for the electron dynamics introduced by the defect states [49].…”
Section: B Effects Of Vacancies On the Hhg Spectramentioning
confidence: 99%
“…There are various theoretical predictions for the HHG from doped semiconductors by using simple onedimensional model Hamiltonians. [38][39][40] In ref., 38 by using TDDFT, it is predicted that there is an enhancement of several orders of magnitude in the efficiency of HHG in a donor-doped semiconductor. Using an independent particle model, Huang et al contrastingly found that the efficiency of the second plateau from the doped semiconductor is enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…After a pioneering work of Ghimire et al 2 , HHG in solids has opened the door to study the electronic structure and its dynamics with the characteristic timescale in solids 1,3 . In recent years, HHG in solids has employed to explore several exciting processes such as band structure tomography [4][5][6] , probing the dynamics of the defects in solids 7,8 , the realisation of petahertz current in solids 9,10 , Bloch oscillations 11,12 are few to name. Moreover, HHG in solids offers an attractive all-solid-state compact optical device to obtain coherent and bright attosecond pulses in extreme ultraviolet energy regime 1,3,13 .…”
Section: Introductionmentioning
confidence: 99%